A generalized class of close-to-convex functions / Shaharuddin Cik Soh - Cik Soh, Shaharuddin (2009)
This class of functions is known as close-to-convex with the concentration on the generalization of the class. The thesis is concerned in finding the extremal properties and radius of convexity for functions in the class G(a, 8, y). Approximations for the radius of stalkiness, convolution properties are obtained and determination of the second Hankel determinant is discussed.